Edukasi Siswa SMAN 1 Batulayar Melalui Penyuluhan Potensi Energi Terbarukan Menuju Sekolah Ramah Lingkungan - Agung Budi Muljono; I Made Ari Nrartha; I Made Ginarsa; Sudi Mariyanto Al Sasongko; I Ketut Perdana Putra; Sultan Sultan; Made Sutha Yadnya (Jurnal Gema Ngabdi, 2023)
Senior High School (SHS) 1 Batulayar is located at Jl. Otomotif Raya, Senteluk, Batulayar, West Lombok Regency, West Nusa Tenggara 83355, Indonesia, is in the Senggigi tourism buffer area. In the 2023 academic year, SHS 1 Batulayar only received 39 new students who were accommodated in 1 class (study group). Seeing these conditions is a problem faced by SHS 1 Batulayar in getting students. As a teaching team in the Department of Electrical Engineering, we are inspired to educate students and teachers, one of which is providing information on the potential of new renewable energy towards environmentally friendly schools. Educational material in the form of knowledge about the new energy sector in accordance with Law No. 30 of 2007 concerning Energy and PP No. 70 of 2009 concerning energy conservation and Minister of Environment and Forestry Regulation No. P.52/MENLHK/SETJEN/KUM.1/9/2019, movement for environmental care and culture in schools, especially in the field of EBT, energy conservation towards the Adiwiyata (Green School) program. The PkM group consists of lecturers, technicians and students from the Electrical Engineering study program specializing in electrical power systems and telecommunication. PkM participants were 25 classes X and More attention to SHS 1 Batulayar which has less number of students.